Key technologies of heterogeneous compatibility in overlay SDN - Zhilan HUANG; Yongbing FAN; Nan CHEN; Xiaowu HE (Dianxin kexue)
Cloud computing scale development provides a new chanllenge to data center network.Data center network is required virtulizing by SDN in order to meet flexible dynamic network requireement under multi-rent environment.SDN is the core technology to realize data center virtulization.The key technology of overlay SDN network virtualization was studied,the compatibility problems remained in commercial overlay SDN products was discussed,the main methods to solve this problem was analyzed,and finally an new overlay SDN architecture based on open source software and white-box switch that could work in heterogeneous hypervisors environment was proposed.